Pengaruh Brand Image terhadap Perceived Service Quality, Kepuasan, dan Loyalitas - Dewanto, Aryo; Rochman, Fatchur; David (Jurnal Aplikasi Manajemen, 2014)
This study aims to examine the influence of brand image on patients'who perceived service quality, satisfaction, and loyalty in outpatient units.This Research conducted on May 2014 was a correlational and quantitative study. The research sample were 109 patients of outpatient units in Ben Mari Hospital Malang. Data were collected by a fivepoint Likert scale questionnaire in which consists of statements about brand image, patients'perceived service quality, satisfaction, and loyalty. The data were analysed by Structural Equation Modeling using Partial Least Squares. The result of the study shows that brand image has a direct and indirect effect on patients'perceived service quality, satisfaction, and loyalty . Brand image has the biggest effect directly on patients'perceived service quality. One of indirect effects of brand image on patient loyalty occurs through patients'perceived service quality and satisfaction. Brand image influences patients'perception on service quality, in turn it infuences patients'satisfaction and loyality. The influence of brand image shows that brand image must be managed by the hospital well and seriously in order to build a positive thought from the patients. Finally, the hospital management image will give the result on patients'acceptance towards the hospital response to their preferences and needs.